Three-year Efficacy and Safety of Takeda's Dengue Vaccine Candidate (TAK-003). (4th October 2021) - Rivera, Luis; Biswal, Shibadas; Sáez-Llorens, Xavier; Reynales, Humberto; López-Medina, Eduardo; Borja-Tabora, Charissa; Bravo, Lulu; Sirivichayakul, Chukiat; Kosalaraksa, Pope; Martinez Vargas, Luis; Yu, Delia; Watanaveeradej, Veerachai; et al.
Abstract: Background: Takeda's live attenuated tetravalent dengue vaccine candidate (TAK-003) is under evaluation in a long-term clinical trial across 8 dengue-endemic countries. Previously, we have reported its efficacy and safety in both seronegative and seropositive participants and that its performance varies by serotype, with some decline in efficacy from first to second year postvaccination. This exploratory analysis provides an update with cumulative and third-year data. Methods: Healthy 4–16 year olds (n = 20099) were randomized 2:1 to receive TAK-003 or placebo (0, 3 month schedule). The protocol included baseline serostatus testing of all participants and detection of all symptomatic dengue throughout the trial with a serotype specific reverse transcriptase-polymerase chain reaction. Results: Cumulative efficacy after 3 years was 62.0% (95% confidence interval, 56.6–66.7) against virologically confirmed dengue (VCD) and 83.6% (76.8–88.4) against hospitalized VCD. Efficacy was 54.3% (41.9–64.1) against VCD and 77.1% (58.6–87.3) against hospitalized VCD in baseline seronegatives, and 65.0% (58.9–70.1) against VCD and 86.0% (78.4–91.0) against hospitalized VCD in baseline seropositives. Efficacy against VCD during the third year declined to 44.7% (32.5–54.7), whereas efficacy against hospitalized VCD was sustained at 70.8% (49.6–83.0). Rates of serious adverse events were 2.9% in TAK-003 group and 3.5% in placebo group during the ongoing long-term follow-up (ie, second half of the 3 years following vaccination), but none were related. No important safety risks were identified. Conclusions: TAK-003 was efficacious against symptomatic dengue over 3 years. Efficacy declined over time but remained robust against hospitalized dengue. A booster dose evaluation is planned. Abstract : This ongoing phase 3 study demonstrated that TAK-003 was efficacious against symptomatic dengue in children and adolescents in a varied epidemiological setting across 8 dengue-endemic countries over 3 years postvaccination, and supports the utility of TAK-003 in dengue control.